دور التحول الرقمي في تحسين الأداء الخدمات المقدمة دراسة حالة مؤسسو إتصالات الجزائر بالولاية الوادي - نريمان, بابه; رجاء, العمودي; شيماء, نصرات (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة إلى معرفة دور التحول الرقمي في تحسين الأداء الخدمات المقدمة، دراسة حالة المؤسسة إتصالات الجزائر بولاية الوادي، ولتحقيق هدف الدراسة اعتمدنا على المنهج الوصفي التحليلي، وتمثلت متغيرات الدراسة في أبعاد التحول الرقمي (الإستراتجية الرقمية، البنية التحتية، القيادة الرقمية، الثقافة الرقمية) وتحسين أداء الخدمات المقدمة. تم استخدام الاستبيان كأداة لجمع البيانات، وبلغ مجتمع الدراسة 50 العمال من إطارات المؤسسة محل الدراسة، وباستخدام برنامج SPSS.V29 لتحليل البيانات توصلت الدراسة إلى وجود دور التحول الرقمي في تحسين أداء الخدمات المقدمة بالمؤسسة إتصالات الجزائر بولاية الوادي، ووجود علاقة ذو دلالة إحصائية بين البنية التحتية و القيادة الرقمية في تحسين أداء الخدمات المقدمة وعدم وجود دلالة إحصائية مع الاستراتيجية الرقمية والثقافة الرقمية، كما أوصت الدراسة بضرورة وجود التحول الرقمي داخل المؤسسة من أجل تطوير وتحسين أداء خدماتها للزبائن بأقل تكلفة ووقت أسرع.This study aimed to know the role of digital transformation in improving the performance of the services provided, a case study of the institution, Algeria Telecom, in the state of El Oued, and to achieve the goal of the study, we relied on the descriptive analytical approach, and the study variables were represented in the dimensions of digital transformation (digital strategy, infrastructure, digital leadership, digital culture) and improve the performance of the services provided. The questionnaire was used as a tool for data collection, and the study population consisted of 50 workers from the frameworks of the institution under study, and using the SPSS.V29 program for data analysis, the study concluded that there is a role for digital transformation in improving the performance of services provided by the institution, Algeria Telecom, in the state of El Oued, and the existence of a statistically significant relationship between the structure Infrastructure and digital leadership in improving the performance of services provided and the lack of statistical significance with the digital strategy and digital culture, the study also recommended the need for digital transformation within the organization in order to develop and improve the performance of its services to customers at the lowest cost and the fastest time.
Keywords: التحول الرقمي ، الأداء الخدمات ، إتصالات الجزائر،